Study of Oblique Propagating Whistler Mode Waves in Presence of Parallel DC Electric Field in Magnetosphere of Saturn - Kaur, R.; Pandey, R. S. (Advanced Electromagnetics, 2017)
In this paper whistler mode waves have been investigated in magnetosphere of Saturn. The derivation for perturbed distribution function, dispersion relation and growth rate have been determined by using the method of characteristic and kinetic approach. Analytical expressions for growth rate and real frequency of whistlers propagating oblique to magnetic field direction are attained. Calculations have been performed at 6 radial distances in plasma sheet region of Saturn’s magnetosphere as per data provided by Cassini. Work has been extended for bi-Maxwellian as well as Loss-cone distribution function. Parametric analysis show that temperature anisotropy, increase in number density, energy density and angle of propagation increases the growth rate of whistler waves along with significant shift in wave number. In case of Loss-cone distribution, increase in growth rate of whistlers is significantly more than for bi-Maxwellian distribution function. Generation of second harmonics can also be seen in the graphs plotted. It is concluded that parallel DC field stabilizes the wave and temperature anisotropy, angle of propagation, number density and energy density of electrons enhances the growth rate. Thus the results are of importance in analyzing observed VLF emissions over wide spectrum of frequency range in Saturnian magnetosphere. The analytical model developed can also be used to study various types of instabilities in planetary magnetospheres.